2013
DOI: 10.29333/ejgm/82253
|View full text |Cite
|
Sign up to set email alerts
|

Hypohydrotic Ectodermal Dysplasia in Black Africans

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The proportion of patients who are completely edentulous are higher in men. This was in concordance with a study done previously (Samaila et al, 2013). Another study showed a contradicting result in men : women ratio of completely edentulous patients as 1:4 (Carr et al, 1993;Kotkin, 1985;Marcus et al, 1996).…”
Section: Resultssupporting
confidence: 93%
“…The proportion of patients who are completely edentulous are higher in men. This was in concordance with a study done previously (Samaila et al, 2013). Another study showed a contradicting result in men : women ratio of completely edentulous patients as 1:4 (Carr et al, 1993;Kotkin, 1985;Marcus et al, 1996).…”
Section: Resultssupporting
confidence: 93%
“…[8][9][10][11][12] Familusi et al reported the first ED case in Nigeria [13] in 1975. Following this, many cases of ED have subsequently been reported in Nigeria [14][15][16][17][18] , but no single case has been reported on ophthalmic manifestations in Nigerian subjects.…”
Section: Introductionmentioning
confidence: 99%